Usefulness of computed tomography and magnetic resonance imaging in radiotherapy planning for the treatment of brain tumors - Benavides, Henry; Celeita, Nathalia; Rodriguez, Diana Milena [UNESP]; Perez, Felipe [UNESP]; Soares da Silva, Alexandre Redson [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Univ Federal Rural Pernambuco, 2011)
Advanced diagnostic techniques such as magnetic resonance imaging and computed tomography have become useful tools for confirmation of presumptive diagnosis of structural lesions in the brain such as encephalic neoplasms in small animal veterinary practice in Colombia, allowing an effective treatment planning that is more specific and less invasive for this type of pathology.
Keywords: Encephalic tumors; computed tomography; magnetic resonance imaging; radiotherapy